Dependence Of V2O5 Nanorods Propertis On Substrate Type Prepared By Simple Hydrothermal Method - Abd-Alghafour, N. M.; Naeem, Ghassan Adnan; Mohammad, Sabah M. (2019)
Vanadium pentoxide (V2O5) nanorods were prepared on various substrates by simple hydrothermal method. The structural characterizations of V2O5 nanorods (NRs) have been studied by using X-ray diffraction analysis. The influence of the different substrates on the surface morphology of V2O5 NRs was investigated by field emission scanning electron microscopy (FESEM) technique. The results show that the preferred orientation along (001) plane. Raman spectra indicate that glass substrate has optimum results due to the size and number of the nanorods with lower defects. It can be found from the absorbance of the glass substrate increases ccompared with the other substrates